If the Fed Acts, How Do You React? : The Liftoff Effect on Capital Flows - Hannan, Swarnali (Washington, D.C. : International Monetary Fund, 2015)
After more than six years of ultra-low interest rates, a Fed liftoff (rate hike) is just a matter of time. This paper goes back to history to understand the spillover effect - or what is termed in the paper as the 'liftoff' effect - of the previous five Fed liftoffs on capital flows. Using a dynamic panel framework covering 48 countries (27 advanced economies, 21 emerging markets) over the period 1982-2006, the paper shows that the liftoff effect on capital flows (total private, portfolio) is significantly higher for emerging market economies (EM) than advanced market economies (AM). EM capital flows are hit indiscriminately one quarter before liftoff, suggesting that markets usually price in the liftoff before the actual event. Over time, there is a bit more variation among EM as policy responses/framework can to some extent dampen market reactions. The findings are similar to the unfolding of events during the taper tantrum episode indicating that, even though current circumstances are very different, history could still provide a good guidance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet